Therapeutic microparticles functionalized with biomimetic cardiac stem cell membranes and secretome - Junnan Tang (Nature Portfolio, 2017)
Stem cells exert their beneficial effects through secretion of regenerative factors. Here, the authors take the membranes and secreted factors from cardiac stem cells and generate a synthetic cell-mimicking microparticle, which, on injection in a mouse model of myocardial infarction, improves cardiac function.